2012
DOI: 10.5505/kjms.2012.40085
|View full text |Cite
|
Sign up to set email alerts
|

Acromion types and subacromial distances in symptomatic patients; MRI findings

Abstract: AIM:The aim of this study was to determine the frequency of different acromion types and to compare their subacromial distances in symptomatic patients. METHODS:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…In our study we also find no correlation between acromion types and tear type, and only19.5% of patients have type III acromion. Our findings about acromion type are compatible with literature [21]. A study over 111 rotator cuff tear patients found that smoking is an independent risk factor for cuff tear [18].…”
Section: Discussionsupporting
confidence: 82%
“…In our study we also find no correlation between acromion types and tear type, and only19.5% of patients have type III acromion. Our findings about acromion type are compatible with literature [21]. A study over 111 rotator cuff tear patients found that smoking is an independent risk factor for cuff tear [18].…”
Section: Discussionsupporting
confidence: 82%